Case Report: EGFR-Positive Early-Stage Lung Adenocarcinoma Transforming to Squamous Cell Carcinoma After TKI Treatment - Liao, Jiatao; Li, Yuan; Liu, Chang; Long, Qianqian; Wang, Jialei (Frontiers in Oncology, 2021)
The histological transformation from epidermal growth factor receptor (EGFR)-mutated adenocarcinoma (ADC) to squamous cell carcinoma (SCC) after tyrosine kinase inhibitor (TKI) treatment is rare. We present a case of a patient who transitioned from early-stage primary lung ADC with partial squamous differentiation, EGFR mutation and amplification, to adrenal gland metastasis as SCC with EGFR amplification disappearance 115-months after surgery, during which gefitinib and local radiotherapy were utilized for the metastasis in the right femoral head and mediastinal lymph nodes. This case might indicate a possible mechanism of EGFR inhibition resistance with SCC transition and EGFR amplification loss from the initially well-responding ADC, especially those with SCC or partial squamous differentiation. The optimal post-progression therapy for ADC-SCC patients is challenging and further studies are needed.